JUDICIALIZATION OF VULNERABILITY: THE BPC AND THE URGENCY OF SOCIAL PROTECTION THROUGH THE MANDAMUS OF MANDAMUS - Lima Neto, Alexandre Moura; Mello, Ana Paula Galvão; Costa, Flávio Vinícius Araujo; dos Santos, Diogo de Almeida Viana; Madureira, Amanda Silva; Leite, Silvio Mesquita; Santana, Guilherme Saldanha; de Miranda, Sara Barros Pereira; de Aguiar, Alessandra Anchieta Moreira Lima; Milhomem, Maria José Carvalho de Sousa (Seven Editora, 2025)
This article examines the effectiveness of the writ of mandamus as a legal instrument to ensure the timely analysis of requests for the Continuous Cash Benefit (Benefício de Prestação Continuada – BPC) within the scope of the National Institute of Social Security (Instituto Nacional do Seguro Social – INSS). Adopting an approach centered on fundamental rights and the protection of individuals in situations of social vulnerability, the study discusses the bureaucratic and judicial obstacles faced by BPC applicants, as well as the role of the Judiciary in safeguarding social rights. The research is based on bibliographic methodology, drawing on recent publications, legal norms, and jurisprudence. It concludes that although the writ of mandamus is not a definitive solution, it proves to be an effective tool for protecting rights violated by administrative inaction.DOI: https://doi.org/10.56238/sevened2025.021-067